Coumarins from Magydaris pastinacea as inhibitors of the tumour-associated carbonic anhydrases IX and XII: isolation, biological studies and in silico evaluation. (1st January 2020) - Fois, Benedetta; Distinto, Simona; Meleddu, Rita; Deplano, Serenella; Maccioni, Elias; Floris, Costantino; Rosa, Antonella; Nieddu, Mariella; Caboni, Pierluigi; Sissi, Claudia; Angeli, Andrea; Supuran, Claudiu T.; et al.
Abstract: In an in vitro screening for human carbonic anhydrase (hCA) inhibiting agents from higher plants, the petroleum ether and ethyl acetate extracts of Magydaris pastinacea seeds selectively inhibited hCA IX and hCA XII isoforms. The phytochemical investigation of the extracts led to the isolation of ten linear furocoumarins (1 –10 ), four simple coumarins (12 –15 ) and a new angular dihydrofurocoumarin (11 ). The structures of the isolated compounds were elucidated based on 1 D and 2 D NMR, MS, and ECD data analysis. All isolated compounds were inactive towards the ubiquitous cytosolic isoform hCA I and II ( K i  > 10, 000 nM) while they were significantly active against the tumour-associated isoforms hCA IX and XII. Umbelliprenin was the most potent coumarin inhibiting hCA XII isoform with a K i of 5.7 nM. The cytotoxicity of the most interesting compounds on HeLa cancer cells was also investigated.